New gymnospermous woods from the Permian of the Parnaíba Basin, Northeastern Brazil, Part II: Damudoxylon, Kaokoxylon and Taeniopitys - Kurzawe, Francine; Iannuzzi, Roberto; Merlotti, Sheila; Rohn, Rosemarie [UNESP] (Elsevier, 2013)
This is the second contribution on the Permian permineralized flora of the Parnaíba Basin, NE Brazil that focuses on the gymnosperm woods from the Motuca Formation. We describe five new species of gymnospermous woods Damudoxylon buritiranaense sp. nov., Damudoxylon humile sp. nov., Damudoxylon roessleri sp. nov., Kaokoxylon punctatum sp. nov. and Taeniopitys tocantinensis sp. nov., and one new form, Taeniopitys sp. 1. The woods vary widely in their anatomy, mainly in their pith features, from simple parenchymatic to solenoid piths with canals and ducts, as well as different cells, such as secretory and sclerenchymatic ones. However, they have one characteristic in common - araucarian pitting in the radial walls of the tracheids. © 2013 Elsevier B.V.
Keywords: Parnaíba Basin; Permian; Permineralized gymnosperm wood; anatomy; cell organelle; gymnosperm; new species; taxonomy; wood; Brazil; Parnaiba Basin; Araucaria; Gymnospermae; Solenoidea